Southeast Asian low-cost carrier airline competitiveness: A solution for economic growth - Phoom Srisook (My University, 2017)
In 2016, low-cost carrier (LCC) passengers represented 53% of the all airline passengers in Southeast Asia, with new aircraft deliveries in 2017 expected to increase by 11%.In Thailand, LCCs in 2016 represented 44.9% of all passengers through Thailand's 6 major airports, which represented 54.7 million passengers out of a total of 122 million air travelers.Competition however amongst the LCCs has become fierce, with fare reductions being a common tactic to fill seats.This study, therefore, developed a questionnaire which included 58 items on passenger characteristics, the LCC service marketing mix, service quality, passenger expectations, and LCC competitiveness along with their 18 related observed variables.Multistage random sampling was employed to obtain 320 passenger respondents who were departing on either Thai AirAsia, Thai Lion Air, Thai Smile, or Nok Air from one of Bangkok's two main airports.Results determined that the service marketing mix plays the most important role in an LCC's competitiveness.
Keywords: Low-cost carrier; Aviation Industry Analysis and Trends